Legume crop genomics - Wilson, Richard F. (AOCS Press, 2011)
The purpose of this book is to document the initial research strategies, the development of genomic tools and resources, and the legume-community consensus on the research objectives that will guide the genomic characterization of major legume crops. This book will present this technical theme in a manner that should help many readers answer the question, "What is genomics?" And finally, this book should help readers formulate an opinion on the question, "Why is genomic research needed?" In considering that query, we hope this publication has shown that genomics represents a quantum leap in technology. The application of this technology in legume crop enhancement will ensure that U.S. agriculture remains competitive in domestic and global markets for legumes and legume crop products.